Pengaruh Pemberian Minyak Zaitun terhadap Penurunan Skala Pruritus pada Pasien yang Menjalani Hemodialisa - Fitri Nur’aini; Kurnia Wijayanti; Indra Tri Astuti (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Pruritus, or itching, varies in duration, location, and severity, and can occur in specific areas or across the entire body surface. Common pharmacological treatments include antihistamines, emollients, topical capsaicin, opioid antagonists, gabapentin, immunomodulators, immunosuppressants, tacrolimus ointment, and oral activated charcoal. Itching in patients undergoing hemodialysis is a common problem that significantly impacts patient comfort, making effective management necessary. Olive oil is known for its anti-inflammatory and moisturizing properties, which may help alleviate pruritus. This study aims to examine the effect of olive oil administration on the reduction of pruritus scores in hemodialysis patients at RSI Sultan Agung Semarang. The study used a quantitative design with a quasi-experimental pre-post two-group comparison model. The sample consisted of 42 hemodialysis patients divided into two groups: the intervention group, which received olive oil and antihistamine, and the control group, which only received antihistamine. The results showed that the average pruritus score before treatment in the intervention group was 5.625, and after administration of olive oil + antihistamine, it decreased to 3.375. Statistical analysis using the Paired Samples Test showed a significant effect of olive oil + antihistamine administration on pruritus reduction (p = 0.000 < 0.05). Furthermore, there was a significant difference in effectiveness between the intervention group (olive oil + antihistamine) and the control group (antihistamine only), with a p-value of 0.000 < 0.05. In conclusion, the administration of olive oil combined with antihistamines is more effective than antihistamine alone in reducing pruritus scores in hemodialysis patients at RSI Sultan Agung Semarang.